2015
DOI: 10.1371/journal.pone.0122604
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis as a Biological Response in Receptor Pharmacology: Evaluation by Fluorescence Microscopy

Abstract: The activation of G-protein coupled receptors by agonist compounds results in diverse biological responses in cells, such as the endocytosis process consisting in the translocation of receptors from the plasma membrane to the cytoplasm within internalizing vesicles or endosomes. In order to functionally evaluate endocytosis events resulted from pharmacological responses, we have developed an image analysis method –the Q-Endosomes algorithm– that specifically discriminates the fluorescent signal originated at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…At this respect, we after sustained treatments (Berger andWhistler, 2010, Whistler, 2012). Moreover, we also described in these same cells that co-activation of 5-HT 2A receptors facilitated the endocytosis of MOP receptors upon morphine treatment similarly as we later A C C E P T E D M A N U S C R I P T 20 described in an analogous experimental model expressing 5-HT 2C receptors instead (Campa et al, 2015, Lopez-Gimenez et al, 2008. Although rather speculative in terms of translating in vitro results obtained from heterologous systems to native or physiological models, these results may suggest future approaches to further explore the biological mechanisms implicated in the improvement of morphine analgesia by enhancing serotonergic neurotransmission.…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…At this respect, we after sustained treatments (Berger andWhistler, 2010, Whistler, 2012). Moreover, we also described in these same cells that co-activation of 5-HT 2A receptors facilitated the endocytosis of MOP receptors upon morphine treatment similarly as we later A C C E P T E D M A N U S C R I P T 20 described in an analogous experimental model expressing 5-HT 2C receptors instead (Campa et al, 2015, Lopez-Gimenez et al, 2008. Although rather speculative in terms of translating in vitro results obtained from heterologous systems to native or physiological models, these results may suggest future approaches to further explore the biological mechanisms implicated in the improvement of morphine analgesia by enhancing serotonergic neurotransmission.…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…In relation to the facilitation of the endocytosis, that result was equivalently obtained with the high homologous 5-HT2C receptor [14]. During the course of our studies with 5-HT2A receptors, we demonstrated that the inhibition of its coupling to Gαq/11 proteins by using the YM254890 compound aborted the facilitation of MOP receptor endocytosis by morphine [13].…”
Section: Introductionmentioning
confidence: 53%
“…Actually, the inability of morphine to endocytose MOP receptors upon activation may be overcome since under particular circumstances the internalisation of MOP receptors by morphine is possible, essentially by overexpression of accessory proteins involved in G-protein coupled receptor endocytosis mediated by agonist binding, principally GRK2 and -arrestin2 among others [5,11,12]. We recently described that the co-activation of either 5-HT2A or 5-HT2C serotonin receptor subtypes facilitates the endocytosis of MOP receptors promoted by morphine when co-expressed in Flp-In TM T-REx TM 293 cells [13,14]. In the case of 5-HT2A receptors, we demonstrated that this facilitation is dependent on receptor coupling to Gq/11 subunits and subsequent PKC activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests an intracellular mode of action of the nigritoxin. Consequently nigritoxin may not act as a host receptor agonist or antagonist, triggering signal transduction pathways 22 , although accumulating evidences revealed that the endocytosis of receptor–ligand contributes to generate cellular signals 23 , 24 . Finally although nigritoxin causes chromatin damage, it is not translocated into the nuclear compartment, such as cytolethal distending toxins 25 .…”
Section: Discussionmentioning
confidence: 99%